Prof. Nguyen Van Khang: A lifetime of dedication to mechanics and educating the young generation - Dien, Nguyen Phong; Hoang, Nguyen Quang (Vietnam Journal of Mechanics, 2025)
With almost 60 years dedicated to the field of mechanics and the Department of Applied Mechanics, Hanoi University of Science and Technology, Prof. Dr. Sc., People’s Teacher Nguyen Van Khang made a vital contribution to educating generations of outstanding students in mechanics and mechatronics, as well as to developing multi-body mechanics in Vietnam. His enthusiasm and passion for mechanical research lasted until the final days of his life. With a burning passion and endless creativity, he always strived hard and became the leading professor in Dynamics and Mechatronics in Vietnam. He also built and maintained close scientific cooperation with many famous professors in other countries. In the bottom of the hearts of colleagues, students and his family members, Prof. Khang remains a symbol of an excellent scientist with practical expertise, extensive knowledge and dedication, as well as a steadfast Party member with unwavering determination. The professor’s spirit of dedication to science and teaching will always be a valuable lesson and a motivation for students and successors to follow.